Analisis dan Implementasi Pengalihan Trafik Data (Failover) Akses Internet Pada Dua ISP - Mohammad Taufan Asri Zaen; Ahmad Tantoni (STMIK Budi Darma, 2023)
When accessing various traffic activities on the internet, you have to pay attention to a reliable and stable connection to avoid downtime problems. Downtime or failure to access the internet can have a very disruptive impact on users while accessing the internet network. Using two or more ISPs is the best solution to avoid interference from ISPs due to having backup paths from other ISPs. Failover is a mechanism for merging or redirecting internet data traffic if a technical problem occurs at one of the ISPs to maintain continuity and smooth internet access. Problems arise if the bandwidth on each internet line is different, on the internet line with the lowest bandwidth value there will be full traffic (overload/congestion) which results in users who are diverted to the internet line with congestion conditions will experience delays in accessing the website and run online applications. The problem in this research is that when the internet bandwidth of the ISP-1 line has a download speed of 205Mbps and the ISP-2 line has a download speed of 50Mbps, it will cause overload traffic (overload/congestion) on the ISP-2 line because the bandwidth is only 50Mbps. The aim of this research is to differentiate between load balance and traffic redirection (failover) where the performance results of previous research are with the performance of failover research on 2 ISPs with different download and upload bandwidth speeds. This research will discuss the analysis and implementation of data traffic redirection (failover) for internet access on two ISPs with simultaneous performance on both ISPs and failover on 2 ISPs with different download and upload bandwidth speeds